Prevalence of Musculoskeletal Disorders among Health Sciences Student Tablet Users at Naresuan University - นามวงษา, สุวลี; กิตติตระการ, ธารารัตน์; โมราสุข, โยษิตา; สุขวิเศษ, พัณณิตา; วงษ์จีน, วโรชา (Journal of Health Science of Thailand, 2024)
The purposes of this study were to explore the prevalence of musculoskeletal disorders and to compare their affected body regions among tablet-using Health Science students at Naresuan University. A questionnaire survey was conducted among 555 participants. It was found that 397 participants (71.53%) had musculoskeletal disorders after using their tablet. The highest prevalence of musculoskeletal disorders in the past 7 days and the past 12 months at the neck was 31.99% and 32.49%, respectively; upper back - both sides 17.38% and 15.87%, respectively; and lower back - both sides was 14.61% and 14.86. The second-highest prevalence was at the upper extremities group including shoulder - right side 10.33% and shoulder - both sides 11.08%; wrist and hand - right side 10.83% and 9.57%; and elbow - left side 3.53% and right side 2.27%; and the least prevalence was at the lower extremities group including hip 7.30% and 8.56% for the past 7 days and 12 months, respectively; knee 6.30% and 6.05%; and ankle and foot 4.03% and 7.05%. In conclusion, the Health Science student tablet users at Naresuan University had musculoskeletal disorders in all body regions. The most prevalent was in the spine group, especially the neck area.